PENGARUH ATMOSPHERE TOKO DAN KEBIJAKAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DI GIANT TLOGOSARI SEMARANG - Perkasa, Aditya; Prihatini, Apriatni Endang (Jurnal Ilmu Administrasi Bisnis, 2018)
In retail business competition, retailers are required to provide a fun shopping experience to consumers. This is due to changes in consumer lifestyles that make shopping activities not only as the fulfillment of economic needs, but evolved into prestige and shopping experience. Strategy that can be used by retailers that pay attention to store atmosphere and price policy. This study aims to determine the effect of store atmosphere and price policy on purchasing decisions at Giant Hypermarket Tlogosari. Type of research used is exsplanatory research. Sampling technique using non-probability sampling. Respondents in this study amounted to 96 respondents. Data collection using questionnaires and using Label scale. Data processing such as validity test, reliability, simple regression, multiple regression, cross tabulation (crosstab), T test, and F test using SPSS version 22.0 software. The results showed that all independent variables in this study have a positive and significant influence on the dependent variable. Positive and significant results are also obtained when the two independent variables are associated with the dependent variable simultaneously